Analisis Kesesuaian Habitat, Struktur, Komposisi Dan Keanekaragaman Pohon Pada Habitat Orangutan Tapanuli Di Koridor Hutaimbaru: Analysis of Habitat Suitability, Structure, Composition, and Tree Diversity in the Tapanuli Orangutan Habitat in the Hutaimbaru Corridor - Tanjung, Dede Syahputra; Aththorick, T. Alief; Rahmawaty, Rahmawaty (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
The Tapanuli orangutan (Pongo tapanuliensis), currently classified as critically endangered, inhabits the Batang Toru Ecosystem and persists in two wild populations. This study aims to analyze habitat suitability for the Tapanuli orangutan, the Importance Value Index (IVI), the Shannon Diversity Index (H′), and the Margalef Species Richness Index (Dmg) of tree species. Model accuracy, assessed by the Area Under the Curve (AUC) of a random test based on 25% of samples, was 0.993, while the overall predictive AUC reached 0.996, both classified as “excellent.” Elevation, precipitation, and distance from forest cover emerged as the most influential environmental variables. Habitat suitability classification revealed 60.23% as “unsuitable,” 28.77% as “suitable,” and 11.00% as “highly suitable.” In secondary forest, the highest IVI values were observed for hoteng (Lithocarpus hystrix) at 28.68%, mayang (Palaquium gutta) at 22.55%, and hayu horsik (Ilex pleiobrachiata) at 17.81%. In mixed gardens/agroforestry systems, durian (Durio zibethinus) had an IVI of 21.44%, mayang (Palaquium gutta) 18.82%, and medang (Persea declinata) 18.48%. Shannon diversity (H′) was high in both secondary forest (3.19) and mixed gardens/agroforestry (3.23), while stem density diversity was moderate in secondary forest (2.71) and mixed gardens/agroforestry (2.53). Margalef richness (Dmg) was high in both secondary forest (5.63) and mixed gardens/agroforestry (5.96), whereas stem richness was high in secondary forest (4.51) but moderate in mixed gardens/agroforestry (3.79).